2018
DOI: 10.3390/toxins10120525
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Identification of Aspergillus Section Flavi in the Context of the Emergence of Aflatoxins in French Maize

Abstract: Aflatoxins (AFs) are secondary metabolites produced by Aspergillus section Flavi during their development, particularly in maize. It is widely accepted that AFB1 is a major contaminant in regions where hot climate conditions favor the development of aflatoxigenic species. Global warming could lead to the appearance of AFs in maize produced in Europe. This was the case in 2015, in France, when the exceptionally hot and dry climatic conditions were favorable for AF production. Our survey revealed AF contaminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 57 publications
2
30
0
2
Order By: Relevance
“…This was also the case for France, where, in 2015, exceptionally hot and dry climatic conditions caused 6% of maize fields to be contaminated by aflatoxins. Strains of Aspergillus section Flavi were isolated from maize samples, and A. flavus was the prevalent species (69% of strains), confirming the presence of these potent toxin-producers in fields in France [31], in addition to those reported in Italy before [13,246] and after publication of the report [247].…”
Section: Impact On Aspergillus Flavus and Aflatoxin Contaminationsupporting
confidence: 67%
“…This was also the case for France, where, in 2015, exceptionally hot and dry climatic conditions caused 6% of maize fields to be contaminated by aflatoxins. Strains of Aspergillus section Flavi were isolated from maize samples, and A. flavus was the prevalent species (69% of strains), confirming the presence of these potent toxin-producers in fields in France [31], in addition to those reported in Italy before [13,246] and after publication of the report [247].…”
Section: Impact On Aspergillus Flavus and Aflatoxin Contaminationsupporting
confidence: 67%
“…Of these, 32.2% and 21.1% of the samples presented contamination levels beyond the regulatory limits for aflatoxin B1 and total aflatoxins, respectively. In another survey in France, 6% of 114 maize field samples and 15% of 81 of maize silo samples were found aflatoxin‐positive (Bailly et al., 2018). Moreover, an exposure and risk assessment of aflatoxins intake through consumption of maize products in the adult populations of Serbia, Croatia and Greece, concluded that average aflatoxin intake through the consumption of maize or maize‐based products was between 0.44 and 5.59 ng/kg bw/day (Udovicki et al., 2019).…”
Section: Agricultural Products and Foods Contaminated By Aflatoxinsmentioning
confidence: 99%
“…However, with ongoing global climate changes, AFB1 is predicted to be an emerging threat in areas where it was not previously present [5,6]. Such is the case of several regions of Europe [7,8]. The genotoxic property of AFB1 justifies limiting consumer exposure to this toxin to the greatest extent possible as reflected in worldwide regulations allowing only a few µg of the toxin per kg of food [9].…”
Section: Introductionmentioning
confidence: 99%